Investigation of the microbial communities colonizing prepainted steel used for roofing and walling. Issue 2 (20th December 2016) - Huynh, Tran T.; Jamil, Ili; Pianegonda, Nicole A.; Blanksby, Stephen J.; Barker, Philip J.; Manefield, Mike; Rice, Scott A.
Abstract: Microbial colonization of prepainted steel, commonly used in roofing applications, impacts their aesthetics, durability, and functionality. Understanding the relevant organisms and the mechanisms by which colonization occurs would provide valuable information that can be subsequently used to design fouling prevention strategies. Here, next‐generation sequencing and microbial community finger printing (T‐RFLP) were used to study the community composition of microbes colonizing prepainted steel roofing materials at Burrawang, Australia and Kapar, Malaysia over a 52‐week period. Community diversity was low and was dominated by Bacillus spp., cyanobacteria, actinobacteria, Cladosporium sp., Epicoccum nigrum, and Teratosphaeriaceae sp. Cultivation‐based methods isolated approximately 20 different fungi and bacteria, some of which, such as E. nigrum and Cladosporium sp., were represented in the community sequence data. Fluorescence in situ hybridization imaging showed that fungi were the most dominant organisms present. Analysis of the sequence and T‐RFLP data indicated that the microbial communities differed significantly between locations and changed significantly over time. The study demonstrates the utility of molecular ecology tools to identify and characterize microbial communities associated with the fouling of painted steel surfaces and ultimately can enable the targeted development of control strategies based on the dominant species responsible for fouling. Abstract : The microbial communities found on painted steel surfaces were geographically distinct and changed significantly over the 52‐week experiment.